UWB Radar for Multiple Human Detection Through the Wall Based on Doppler Frequency and Variance Statistic - Rittiplang, Artit; Phasukkit, Pattarapong (My University, 2019)
Multiple human detection through the wall has become an interesting topic for security, rescue, life detecting under earthquake rubble, etc. This paper presents a UWB radar at 3 GHz for detecting multiple humans through the wall based on Doppler frequency and variance statistic of the respiratory signal. Technically, we have referred to efficiently simple methods are FFT and variance statistic for identifying the respiratory frequency of multiple persons quickly. Experimental results show the methods can identify and evaluate quickly respiratory frequencies of two persons through the wood wall.
Keywords: Doppler frequency; human detection; UWB radar; variance statistic; vital sign signal